Pszenica na rynku światowym - Jankowiak, Ludwik; Makieła, Marek (Wydział Prawa i Administracji UAM, 1969)
The first part of the paper deals with the analysis of the evolution of world wheat trade covering the period of 1934 -1967. The main regions of production, export and import of wheat have been characterized. The said analysis comprises the quantitative as well as qualitative aspects of the wheat market — it has, at the same time, a practical, economic overtone. This last aspect becomes clearer if we take into account, that wheat provides humanity with l/5th of all the consumed calories and occupies about 32% of the word cultivable land. Wheat takes the first place in the world's agricultural and food trade (representing over 60% in the world's grain tonnage). The authors devoted much attention to the problem of regulating the level of wheat prices according to the world scale. The last part of the paper concentrates on various aspects of international economical cooperation for the purpose of maintaining equilibrium on world wheat market.
Wheat on World Market